Isosporosis and unizoite tissue cysts in patients with acquired immunodeficiency syndrome - Velásquez, Jorge Néstor (2001)
Fil: Velásquez, Jorge Néstor. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Parasitología; Argentina